Study on Mortality of Kikar (Acacia nilotica) in Punjab - Luna, R. K.; Kaushal, P.; Banyal, R. (Indian Forester, 2006)
The present study is an attempt to address the problem of large scale mortality of Kikar trees in Punjab by analysing all the possible factors including climatic, entomological, pathological and miscellaneous. The results of the present investigation reveal that mortality is site specific and its intensity is governed by the dominance of either environmental or miscellaneous factors, which acted as pre-disposing factors. The observations also indicated that young plantations were mostly affected due to severe intensity of fog and frost, whereas, the older plantations were affected mostly due to insects pests and pathogens as they got predisposed due to continuous spell of unfavourable conditions. Among the pathogens, Ganoderma lucidum was found to be responsible for causing mortality. The insect pests which were found to be associated with mortality, are Celostrena scabrator, termites, caterpillars of Selepa celtis and Indarbela quadrinotata and nymphs of Acaudeleyrodes rachipora.